Real-time implicit bulging and area preservation - LINDEN, NIALL; REYNOLDS, HUGH; O'SULLIVAN, CAROL ANN (My University, 2000)
Implicit Surfaces are particularly suitable for the animation of deformable objects, although some problems still remain, especially in real time applications. One problem is that of volume loss when objects are squashed. This paper presents a real time solution for the preservation of volume using dynamic creation of primitives in two dimensions. We also look at the unwanted blending problem and propose a more efficient solution.
PUBLISHED
Keywords: Implicit Surfaces; Volume Preservation